Dietary trends among czech school children between 2002-2014: HBSC study - Jaroslava Voráčová; Sigmund Erik; Dagmar Sigmundová (Palacký University Olomouc, 2015)
BACKGROUND: Unhealthy eating habits and insuffi cient physical activity are common among children and adolescents and are associated with overweight/ obesity which is one of the risk factors of chronic diseases. Recent evidence shows that many children skip breakfast, do not eat recommended amount of fruit and vegetables and consume high amounts of sweets and soft drinks. There is not a good understanding of the changes in eating behaviours of Czech schoolchildren in relation to their age and gender. OBJECTIVE: The aim of this study was to analyze the trends in eating behaviours (regular consumption of fruit, vegetables, sweets, soft drinks and breakfast during weekdays and at the weekend) of 11, 13 and 15 year old boys and girls between 2002 and 2014. METHODS: The data was used from a Czech survey of the International HBSC Study collected in 2002, 2006, 2010 and 2014. Participants were randomly selected from all regions and districts of the Czech Republic. The eating behaviours were measured by a standardized questionnaire that was completed by children attending 5th, 7th and 9th grades of primary schools between April and June. Trends in eating behaviours were analyzed by logistic regression analyses for each eating behaviour and gender (boys, girls) and age (11, 13, 15 years). RESULTS: Between 2002 and 2014, the fi ndings showed a decrease in number of children and adolescents that reported regular consumption of sweets (p < .01), soft drinks (p < .001) and fruit (p < .01). An increase of daily breakfast consumption during weekdays was also documented, however, signifi cent changes in  consumption were indicated only in girls (p < .001). No signifi cant change was monitored in daily vegetable consumption and breakfast at weekends. More frequent daily fruit, vegetable and breakfast (at weekend) consumption was reported by girls and younger children whereas daily soft drink and breakfast (during weekdays) intake was more prevalent in boys. CONCLUSIONS: The results of this study provided an insight into current food habits of the Czech children and adolescents as well as described the changes of these behaviours from 2002–2014. These fi ndings indicated the need for re-evaluation of current national policies, nutrition requirements and regula tions and new intervention programs to improve eating habits of Czech children.